Implicit communication in multi-robot systems with limited sensing capabilities - Loizou, Savvas; Constantinou, Nicolas (My University, 2021)
The method presented in this paper exploits the concept of Control-Coding to enable the implicit transfer of binary information between agents in multi-robot systems. Binary sequences are encoded into the robot's control action by overlaying secondary control signals on top of the primary control signal, thereby forming a controller-encoder pair which simultaneously (i) stabilizes the robot with respect to its control objective, and (ii) transmits information through the motion of the robot. This motion can be detected and decoded by other robots, so as to extract the transmitted information. The effectiveness of the method is demonstrated by simulating a simple coordination task between two unicycles with limited sensing and non-existent communication capabilities.
Keywords: Control-Coding; implicit communication; limited sensing; Multi-robot systems